Economic Value of Utilizing Manure in Yogyakarta Goat and Sheep Farmers Association: A Partial Budgeting Approach - Trisnanda Fredinabila Ramadhani; Tian Jihadhan Wankar; Tri Anggraeni Kusumastuti (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The utilization of livestock manure from goat and sheep farming presents significant opportunities for farmers to increase the value of their production. This study aimed to identify the various uses of manure by-products, assess their economic impact, and examine factors influencing the sale of these by-products. The sample included 53 respondents, selected through convenience sampling from active members of the Yogyakarta Goat and Sheep Farmers Association (PPKDY). These farmers, engaged in both household and smallholder farming systems, had at least one year of experience and participated in interviews. Data were analyzed using a descriptive quantitative approach, with partial budgeting used to assess the economic impact. Additional income was generated through the sale of both fermented and non-fermented compost, with costs covering raw materials, processing, packaging, and labor. Multiple linear regression analysis was conducted to determine factors influencing manure sales. Results showed that respondents were of productive age (20-64 years), had high education levels, and 5-7 years of farming experience. The most common use of manure was as compost fertilizer and applied to agricultural land, as farmers also grew feed crops and other plants. Economic analysis revealed that non-fermented compost earned IDR 11,050 per sack, while fermented compost earned IDR 14,550 per sack. The study found that factors such as sale type and livestock numbers significantly affected manure sales (P<0.01), with education also influencing sales (P<0.05). This research highlights the importance of recognizing manure as an income source and encourages increased collaboration and technical support through PPKDY.